Mulheres, Gênero e Sexualidades na sociedade diversos olhares sobre a cultura da desigualdade - Brabo, Tânia Suely Antonelli Marcelino (Editora Oficina Universitária, 2020)
WOMEN, GENDER AND SEXUALITIES IN SOCIETY - VARIOUS VIEWS ON THE CULTURE OF INEQUALITY Violence against women has been one of the striking features of Brazilian society and permeates all social classes, often seen naturally. Data from the 2020 Brazilian Yearbook of Public Security show worrying rates of increase: 648 women were victims of femicides in the first half of 2020, i.e. an increase of 1.9% compared to the same period in 2019. This is a historical-cultural finding that requires consistent, systematic educational actions so that people's subjectivities can work, based on values of dignity, respect for human beings, in the conception of the right to difference in equality. Dealing with themes of this nature are essential contributions to the training processes of all people, at all levels of schooling and in all areas of knowledge. This book, therefore, contributes to broaden and strengthen the debate, with a vast and important production, when dealing with violence in its relationship with: Gender, Sexuality and how they are treated in society. Aida Monteiro